ANALISIS KEPUTUSAN IBU NIFAS MEMILIH TEMPAT PERSALINAN DI WILAYAH KERJA PUSKESMAS RAKIT KULIM KABUPATEN INDRAGIRI HULU - Alhidayati Alhidayati; Herlina Susmaneli; Risa Amalia; Feny Primawati (Ensiklopedia of Journal, 2023)
The puerperium is the period after the release of the placenta until the reproductive organs recover as before pregnancy and last for 40 days. Childbirth is a series of events from the time of conception and ends with the expulsion of the baby, followed by the removal of the placenta. The most ideal place for giving birth is a health facility with well equipment and health workers who are ready to help at any time in the event of childbirth complications. According to Mass Central Health of Rakit Kulim data, only 46 mothers gave birth in health service facilities targeting 601 mothers. This study aims to analyze the decision of post partum mothers to choose the place of giving birth. This study use a qualitative type with in-depth interview design. The research variables are influence of knowledge, education level, social culture, access to health services, income, parity and family support. Research informants amount of 7 people, with 2 main informants are postpartum mothers, 4 informants are supporting program holders and postpartum mother families, 1 key informant is the head of the Mass Central Health of Rakit Kulim. The results showed that the knowledge of post-partum mothers is still low, due to the relatively low level of education. Postpartum mothers choose to giving birth at home due to long distances and bad roads condition to get to nearest health facilities. The decision to giving birth at home is determined by the mother herself and also receives support from the family because of the consideration sense of comfort and the cost is not too much. Even though the government has issued policies such as the use of Childbirth Assurance Program (Jampersal).